The Effectiveness of a Voice Care Program Among Primary School Teachers in Northeastern Malaysia - Sundram, Esther Rishma; Norsa’adah, Bachok; Mohamad, Hazama; Moy, Foong Ming; Husain, Nik Rosmawati Nik; Shafei, Mohd Nazri (Oman Medical Specialty Board, 2019)
Objectives: We sought to determine the effectiveness of a voice care program among primary school teachers in a northeastern district in Malaysia. Methods: We conducted a randomized community trial in eight primary schools in a northeastern district in Malaysia. The self-administered and validated Malay-Voice Handicap Index-10 (M-VHI-10) questionnaire was used to assess overall voice handicap scores preintervention and eight weeks post-intervention. Teachers with a score of five or more (n = 86) were randomized into intervention (n = 41) and control groups (n = 45). The intervention group received portable voice amplifiers and vocal hygiene instruction, which was delivered by lectures and a booklet. The control group was not prescribed any intervention. Results: The sociodemographic, lifestyle, and occupational characteristics of the teachers (except maximum number of students per class) were similar between both groups. The baseline M-VHI-10 scores between both groups were also comparable. After the intervention phase, there was a significant effect observed in the total M-VHI-10 scores (p = 0.021, F-stat (df): 5.33 (1,79)) between both groups after controlling for the maximum number of students per class. Conclusions: Our results support the use of voice amplification in adjunct with vocal hygiene instruction as a prevention and treatment modality to reduce voice handicap among teachers. Our study demonstrated encouraging evidence on the low-cost voice care program as well as the success of group and workplace-based approaches in the school setting. © 2019, Oman Medical Specialty Board. All rights reserved.